SENTENCE TYPES ANALYSIS OF INFORMATION AND TECHNOLOGY CONFERENCE PAPER - Kisno Kisno (Universitas Negeri Padang, 2015)
This paper is a research about the sentence types used in an Information and Technology Conference Paper for teaching English for a Specific Purpose in university level. The aim of this research was to find out the most dominant sentence type written by the author majoring in Information and Technology and to investigate why the author frequently used the sentence in the conference paper. The data were taken from a conference paper and 'uvere analyzed using the theory of sentence types by Delahunty and Garvey (2010). The researcher classified and calculated the number of the sentences in the paper based on their types. It was found that four types of sentences were used in writing an IT text. In details, Complex Sentence dominated the text with the number of 43 sentences or 46% of the sentence in the text. Almost 25% of the sentences in the text were in the form of Simple Sentence, and Compound Complex Sentence ranked the third position with 17 sentences and the newest sentences in the paper was Compound Sentence which was only 10 sentences or nearly 11% of the number of sentence in the IT text. To conclude, the author frequently used Complex Sentence in order to give more description about the items the author wrote in the paper.